Right ventricular echocardiographic parameters predict severe sleep apnea syndrome in patients with heart failure - Saoussen Antit; Ferdaous Yangui; Mariem Louati; Amine Boufares; Syrine Abdellatif; Mohamed Ridha Charfi; Lilia Zakhama (Exploration of Medicine)
Aim: The study aimed to determine which right ventricle echocardiography parameters were associated with severe sleep apnea syndrome in heart failure patients with sleep apnea syndrome. Methods: A cross-sectional monocentric study was conducted, including 85 patients with stable heart failure. All patients underwent home respiratory polygraphy and transthoracic echocardiography with evaluation of the right ventricular echocardiographic parameters and sleep apnea syndrome severity. Results: The average age of the population was 69 years. The median left ventricular ejection fraction was 38% (33; 52). Sleep apnea syndrome was diagnosed in 71 patients (83.5%), with obstructive sleep apnea in 50 patients (58.8%) and central sleep apnea in 21 patients (24.7%). Severe sleep apnea syndrome was observed in 31% (n = 22) of patients. In the univariate analysis, right ventricle Tei index with a cutoff value > 0.50 (OR = 3; 95% CI = 1.06–8.56; p = 0.035), right ventricle fractional area change < 40 (OR = 4; 95% CI = 1.38–11; p = 0.09) and right ventricle free wall longitudinal strain with a cut-off value > –17 (OR = 3.5; 95% CI = 1.15–9.41; p = 0.002) increased the risk of having severe sleep apnea syndrome. In the multivariate analysis, the right ventricle free wall longitudinal strain was the only independent predictor for severe sleep apnea syndrome [hazard ratio (HR) = 0.892; 95% CI = 0.816–0.979; p = 0.036]. Conclusions: Right ventricle free wall longitudinal strain seems to be a strong predictor of severe sleep apnea syndrome in patients with stable chronic heart failure and sleep apnea syndrome.